The diversity in antimicrobial resistance of MDR Enterobacteriaceae among Chinese broiler and laying farms and two mcr-1 positive plasmids revealed their resistance-transmission risk - Zong, Shuaizhou; Xu, Dingting; Zheng, Xiner; Zaeim, Davood; Wang, Peng; Han, Jianzhong; Qu, Daofeng (Frontiers in Microbiology, 2022)
This research aimed to investigate the microbial composition and diversity of antimicrobial resistance genes (ARGs) found in Chinese broiler and layer family poultry farms. We focused on the differences in resistance phenotypes and genotypes of multidrug-resistant Enterobacteriaceae (MDRE) isolated from the two farming environments and the existence and transmissibility of colistin resistance gene mcr-1. Metagenomic analysis showed that Firmicutes and Bacteroides were the dominant bacteria in broiler and layer farms. Many aminoglycoside and tetracycline resistance genes were accumulated in these environments, and their absolute abundance was higher in broiler than in layer farms. A total of 526 MDRE were isolated with a similar distribution in both farms. The results of the K-B test showed that the resistance rate to seven antimicrobials including polymyxin B and meropenem in broiler poultry farms was significantly higher than that in layer poultry farms (P≤0.05). PCR screening results revealed that the detection rates of mcr-1, aph(3')Ia, aadA2, blaoxa-1, blaCTX-M, fosB, qnrD, sul1, tetA, and catA1 in broiler source MDRE were significantly higher than those in layers (P≤0.05). A chimeric plasmid p20432-mcr which carried the novel integron In1866 was isolated from broiler source MDRE. The high frequency of conjugation (10-1 to 10-3) and a wide range of hosts made p20432-mcr likely to play an essential role in the high detection rate of mcr-1, aph(3')-Ia, and aadA2 in broiler farms. These findings will help optimize disinfection and improve antimicrobial-resistant bacteria surveillance programs in poultry farms, especially broilers.